Potential use of rare earth oxides as tracers of organic matter in grassland. Issue 2 (20th February 2015) - Senbayram, Mehmet; Bol, Roland; Dixon, Liz; Fisher, Andrew; Stevens, Carly; Quinton, John; Fangueiro, David
Abstract: Tracing organic matter (OM) in soil is challenging, because runoff and leaching processes are interrelated and have multiple sources. Therefore, multiple tracers with low background concentrations such as rare earth element oxides (REOs) are necessary to delineate the origin of sources of the organic materials in groundwater, rivers or in catchments. The main objective of this study was to examine the potential use of REOs as a tracer in various forms of OM (1) whole slurry, (2) solid, and (3) liquid phase of cattle slurry after mechanical separation. A laboratory experiment was carried out using five REOs (La, Gd, Sm, Pr, and Nd oxides) mixed directly into soil or mixed with various fractions of cattle slurry and then applied to the soil surface. In the additional grassland experiment, Gd oxide was spiked with soil and cattle slurry and then applied to the soil surface. The mineral N in the liquid phase (urine) of the slurry in the grassland experiment was labelled with 15 N urea (16 atom%). In the laboratory experiment, results showed that the five REOs concentration of soil in 0–1 cm soil section after the rainfall simulation was still up to 20 times more than the background values. In 1–2 cm soil section, the concentration of only Gd (two fold higher) and La oxides (50% higher) were significantly higher than the soil background values. Therefore, we hypothesized that Gd and La oxides were associated also with relatively finer organic particles in slurry, thus 1–2 cm soil section were enriched with these oxides. The five REOs concentration below 2 cm soil depth were similar to the background values in all treatments. In line with the laboratory experiment, Gd concentrations in the deeper soil layers (2–4 and 4–8 cm) in the grassland experiment were not significantly affected by any treatment. Both in grassland and laboratory experiment, solid phase of the slurry (dung) was collected from the soil surface after rainfall simulation. Here, about 56% of REOs were measured on the solid phase of the slurry which indicates the strong binding potential of REOs on slurry OM. The present novel study, where REO tagged slurry was uniquely tested to study geochemical cycle of organic fertilizers, clearly highlighted the potential for their use as multiple‐tracers of (animal derived‐) OM in agricultural soils.